Transfection of nonmuscle beta- and gamma-actin genes into myoblasts elicits different feedback regulatory responses from endogenous actin genes (The Rockefeller University Press, 1992)
We have examined the role of feedback-regulation in the expression of the nonmuscle actin genes. C2 mouse myoblasts were transfected with the human beta- and gamma-actin genes. In gamma-actin transfectants we found that the total actin mRNA and protein pools remained unchanged. Increasing levels of human gamma-actin expression resulted in a progressive down-regulation of mouse beta- and gamma-actin mRNAs. Transfection of the beta-actin gene resulted in an increase in the total actin mRNA and protein pools and induced an increase in the levels of mouse beta-actin mRNA. In contrast, transfection of a beta- actin gene carrying a single-point mutation (beta sm) produced a feedback-regulatory response similar to that of the gamma-actin gene. Expression of a beta-actin gene encoding an unstable actin protein had no impact on the endogenous mouse actin genes. This suggests that the nature of the encoded actin protein determines the feedback-regulatory response of the mouse genes. The role of the actin cytoskeleton in mediating this feedback-regulation was evaluated by disruption of the actin network with Cytochalasin D. We found that treatment with Cytochalasin D abolished the down-regulation of mouse gamma-actin in both the gamma- and beta sm-actin transfectants. In contrast, a similar level of increase was observed for the mouse beta-actin mRNA in both control and transfected cells. These experiments suggest that the down- regulation of mouse gamma-actin mRNA is dependent on the organization of the actin cytoskeleton. In addition, the mechanism responsible for the down-regulation of beta-actin may be distinct from that governing gamma-actin. We conclude that actin feedback-regulation provides a biochemical assay for differences between the two nonmuscle actin genes.